A Sociolinguistic Approach to ESP Reading Instruction: improving Reading Comprehension of Non-Philology EFL Undergraduates through Genre-Diverse Profession-Oriented Texts - Khudayberdiyeva, Dilnovoz Ilhom qizi (The Lingua Spectrum, 2026)
This study examines the effectiveness of a sociolinguistic approach in English for Specific Purposes (ESP) reading instruction for non-philology economics students in Uzbekistan. The research employed a one-group pre-test/post-test design with 126 participants over a 16-week instructional period. The intervention integrated genre-based teaching, register awareness, and reflective monitoring tasks to enhance students’ reading comprehension. The assessment instrument included genre-diverse texts, multiple-choice questions, situational tasks, and reflective activities. The results revealed statistically significant improvements in all components, with a substantial overall gain in reading performance. The largest effect was observed in genre-based text comprehension, while situational tasks showed the highest score increase. Cross-institutional analysis confirmed the consistency of results across different universities. The findings demonstrate that sociolinguistic instruction not only improves comprehension but also develops pragmatic and professional reading skills. Therefore, the study supports the integration of sociolinguistic ESP methodologies into higher education curricula to enhance students’ communicative competence and professional literacy.